USING CLASSROOM-ENVIRONMENT APPROACH IN DEVELOPING THE STUDENTS’ SPEAKING SKILL AT MTS NW TEGAL - Agus Salim; Jumadil Jumadil (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2016)
This study is aimed to prove that building students’  (MTs NW Tegal) abilities in English is easy. It can be proved from the analysis results before and after the research conducted. The early observation results show that the subject (students class II b) found any difficulties in expressing their ideas by using English. It is proved when they are demanded to introduce themselves, ask and answer the questions. To solve the problem the researcher applied classroom-environment approach. This research was conducted as long as one semester. The processes were started by doing the early observation and pre-test, then continued with teaching-learning process, and ended post-test. Reording was used to collect the data of the study. The recording was analyzed in three procedures, reduction, display and conclusion. The analysis results prove that the students’ abilities in speaking change significant.